Chile with strong trade links to the north and to Asia, Chile aims to be a gateway for trade. (Architectural Record, 1998)
Provides information as it relates to architecture in Chile. Goals of Chile; Information on the construction market; Economic condition of Chile; Description of the Alusa Printing Co., Prolam Building and Chapel of Villa Maria School; Population of Chile; Gross domestic product of Chile for 1997.